PENGARUH PROMOSI, KUALITAS PRODUK DAN BRAND LONGEVITY TERHADAP LOYALITAS PELANGGAN PRODUK KOSMETIK DAN SKINCARE - Priyanka, Felyna (STIE Mahardhika, 2025)
Along with the times, the need for skin care and health is increasing. The high desire of people to look attractive is influenced by trends, social media and the development of innovations and types of cosmetics and skin care products. Appearance is important today because it is an impression for the person himself in the eyes of others. This research aims to determine the effect of promotion, product quality and brand longevity on customer loyalty in cosmetics and skincare products. The population in this study were women in Kartasura who consistently used cosmetic and skincare products. The sample taken in this study was 59 people. This research is a quantitative study using multiple linear regression methods. The variables in this study consist of 3 independent variables, namely promotion (X1), product quality (X2), brand longevity (X3) and the dependent variable customer loyalty (Y). The results show, partially promotion has a significant effect on customer loyalty. Product quality has a significant effect on customer loyalty. Brand longevity has a significant effect on customer loyalty. Simultaneously, promotion, product quality and brand longevity together have a significant effect on customer loyalty.